Silencing of the hPOT1 gene by RNA inference promotes apoptosis and inhibits proliferation and aggressive phenotype of gastric cancer cells, likely through up-regulating PinX1 expression. Issue 12 (21st July 2011) - Wan, Shun-Mei; Tie, Jun; Zhang, Ya-Fei; Guo, Jun; Yang, Liu-Qin; Wang, Jun; Xia, Shi-Hai; Yang, Shi-Ming; Wang, Rong-Quan; Fang, Dian-Chun
Abstract : Background: The human protection of telomeres 1 (hPOT1) protein, a single-strand telomeric DNA binding protein, plays an important role in telomere protection and telomere length regulation. However, its effect on invasion of gastric cancer remains unclear. Aims: To explore the role of hPOT1 in the proliferation and invasion of gastric cancer cells. Methods: The gastric expression of hPOT1 was examined in normal gastric mucosa (n=25), intestinal metaplasia (n=20), gastric dysplasia (n=20) and gastric cancer (n=150) by immunohistochemistry. The mean optical density (MOD) of the immunostaining was determined by semi-quantitative image analysis. The role of hPOT1 in the cell proliferation, apoptosis and invasion of gastric cancer 7901 cells was determined by means of the RNA interference (RNAi) of hPOT1 mRNA. The effects of hPOT1 RNAi on the expression of hPinX1 and hTERT were detected with western blotting. Results: The hPOT1 MOD was progressively increased from the normal mucosa to intestinal metaplasia, dysplasia, and gastric cancer. An increased hPOT1 expression significantly correlated with tumour serosal invasion, node metastasis and advanced stage. Transfection of hPOT1 siRNA into SGC-7901 cells led to a decrease in cell proliferation, colony formation and invasion, and also an increase of apoptosis. An up-regulation of hPinX1 and down-regulation of hTERT were found in gastric cancer cells with hPOT1 siRNA. Conclusions: Increased hPOT1 expression is associated with an advanced tumour stage. hPOT1 RNAi inhibits proliferation and invasion, and induces apoptosis of gastric cancer cells. The effects of hPOT1 RNAi seem to be functionally linked to up-regulation of PinX1 and down-regulation of hTERT.